Implementasi Kebijakan Pengentasan Kemiskinan Melalui Program Bedah Rumah: Studi Kasus di Kecamatan Loloda Utara Kabupaten Halmahera Utara, Maluku Utara - Simson Tondo (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2017)
Along with decentralization, poverty alleviation efforts are not only the responsibility of the central government but also the local government by presenting various policies. One policy that is considered to empower the community is the policy of poverty alleviation through home surgery program conducted by North Halmahera District Government precisely in North Loloda District. The purpose of this research is to analyze the implementation of poverty alleviation policy through home surgery program. The results of this study show the implementation of the home surgery program is not in accordance with the program objectives and expectations of the program itself, this is seen from: First, the lack of communication or socialization directly to the community about the home surgery program. Secondly, the manpower who used to make the house is a Civil Servant who certainly has no expertise in working and making homes and budgets that are not available in the North Halmahera District Budget in 2011 and part of the budget is collected of the contributions of certain parties. Thirdly, local governments do not have a commitment in terms of honesty and democratic, wherein the implementation of programs in the field there are still jobs that are not on the target program and there is injustice in determining target families. Fourth, the implementation of the program is not in accordance with the mechanism as expected because the project of home surgery program is not planned and planned in the Regional Budget in 2011, also some of the funds collected from non-governmental organizations and Civil Servants and labor in use work is a civil servant.